Effects of precooling on physiological and performance response in a warm and humid environment in exercises with intermittent sprinting - Chua, Junhui (2019)
Thermal stress has been a concern for athletes during sporting events, especially in environments with a high ambient temperature and percentage of relative humidity. This purpose of this study is to investigates the effects of 20 minutes of part-body precooling performance and physiological variables during an intermittent sprinting protocol (ISP) in a warm and humid environment. It was hypothesized that precooling will improve performance among athletes of sports with intermittent sprinting. Ten male athletes (age, 24.6 ± 0.96 years) who partake in sports with intermittent sprinting were recruited and randomly assigned to either first perform the control or experimental trial. Precooling was administered during the experimental trial prior to testing. A warm up protocol consisting of jogging 2 rounds around the hockey, static stretches of the quadriceps, hamstrings, groin and calves and running 3 laps between the cones set at 20 metres apart were performed before testing. The ISP is a 20-minute test protocol consisting of 4x5 minute bouts of intermittent sprinting exercise. Each minute, participants would sprint for 5 seconds followed by either hard running, jogging, walking, which is rotated every minute. Results showed significant improvements in total distance covered during the ISP for the experimental trial (p=0.024). There is also a significant effect of precooling on core temperature (p<0.001). However, there were no significant differences between heart rate (p=0.145), rate of perceived exertion (p=0.246), thermal scale sensation (p=0.072) and sweat loss (p=0.177). It was concluded that smaller field-based precooling methods may improve performance during intermittent sprinting exercises.